The moderation effect of uncertainty environment on SME business performance - Sri Setyo Iriani,; Musdholifah, Musdholifah; Kautsar, Achmad (Technium Social Sciences Journal, 2021)
The Covid-19 pandemic has had an impact that has never been felt before by small and medium enterprises (SMEs) business actors in Indonesia. In business, this situation is called environmental uncertainty. Environmental uncertainty is a condition in which a person is constrained to predict the surrounding situation so he tries to do something to deal with the environmental uncertainty. Environmental dynamics with their uncertainties play a positive moderate role between strategic flexibility and firm performance, which is consistent with the results of previous studies. This research method used a mixed research design with a sequential explanatory strategy. The population of this research was SME’s Sidorajo which has the following criteria: doing this business as the main job, running the business for at least 3 years and being active in community development activities and the department. The sample obtained was 100 respondents. The data collection technique was carried out by distributing online questionnaires via google form and FGD with SMEs and Koperindag Office. The results show that business strategy has a positive effect on business performance, strategic flexibility has a positive effect on business performance, environmental uncertainty has a negative effect on business performance and strategic flexibility has no effect on SMEs business performance in Indonesia when moderated by environmental uncertainty. Therefore, environmental uncertainty is not able to play a role as a moderating variable of the influence of strategic flexibility on the performance of SMEs businesses in Indonesia